الوظائف المشتركة والأهداف المنشودة بين المنظمات العالمية الثلاث صندوق النقد الدولي ، البنك الدولي ، المنظمة العالمية للتجارة الدولية وإدارتها للإقتصاد العالمي - بونعاس ،شاكر شايب (جامعة الوادي University of Eloued, 2024)
The transformations that the world economy is experiencing today are giving international trade a new face, the integration of groups of nations, technical progress, and the influence of large multinational firms. The global economic order that emerged after World War II saw the birth of influential global organizations such as the International Monetary Fund (IMF), The World Bank (WB), and the World Trade Organization (WTO). The functions assigned to these organizations made it possible to establish a new world economic order, a stage made up of mutation and changes which pushed many countries to work to find the means of exchange and integration within the economy. worldwide.
Common functions and desired goals between the three global organizationsInternational Monetary Fund, World Bank, World International Trade Organization And its management of the global economy
Keywords: منظمة التجارة العالمية،; البنك الدولي،; صندوق النقد الدولي،; الأسواق المالية والنقدية،; الاستثمار،; :WTO; WB; IMF; FINANCIAL AND MONETARY MARKET; INVEST; DEVELOPMENT